PENGANGKATAN ANAK BEDA KASTA DALAM PERSPEKTIF HUKUM DAN HAK ASASI MANUSIA - I Gede Pasek Pramana; Ni Putu Niti Suari Giri (Faculty of Law, Mahasaraswati University, Denpasar, 2020)
This research has 2 objectives: (1) to find out and analyze the legality of adopting children of different caste; (2) to find out and analyze the responsibility of the state in the case of the cancellation of adopting children of different castes in the context of fulfill, respect and protect human rights. This research is a sociolegal research that examines the problem of adopting children of different caste from a normative perspective and an empirical perspective. Based on the results of the research, it was concluded that the adoption children of different caste is legal act according to positive law in Indonesia. In fact there are still cases of cancellation of the adoption children of different caste in Bali. The state responsibility in implementing efforts to fulfill, respect and protect human rights, the state then intervenes in cases referred to through mediation efforts and/or appointment of trustees.